CARD OF IDENTIFICATION PHYLUM AS AN INOVATIVE MEDIA TO STUDY ANIMAL CLASSIFICATIONS - Lukita Octavia Lukman Putri (University of Muhammadiyah Malang, 2016)
In science teaching and learning, especially Biology, ability to classify things is an important ability. Those ability will help students to distinguishing, agglomerating, categorizing, connecting concepts with or concepts and so on. Based on observation which done on Sumedang region’s schools, we discovered that on Animal Classifications concepts, students have difficulty to understanding the terminology of determination key. Besides, teachers also being interviewed and we collected data that in learning on class, students apparently cheating the determination key to finish their work. From that observation and interview data, we innovated determination key as a media to learn Animal Classifications with creating card of phylum identification. This is a R&D model. The result of this research expected to help students grow their classify ability and help teacher on teaching and learning as a learning media.